Analysis of Mother's Personality , Mother's Parenting Style, and Adolescent 's Autonomy in Rural Families - Naufanni Muthi Aulia; Alfiasari - Alfiasari (Department of Family and Consumer Sciences, Bogor Agricultural University, 2017)
This study design was cross-sectional study. Examples in this study were teenagers and mothers of three selected junior in Ciampea Sub-district. The number of samples in this study were 100 adolescents and mothers who were selected through cluster random sampling. The results showed the tendency of personality type mostwidely owned mom is conscientiousness that a personality type that thorough, orderly, industrious, diligent, efficient, planners, and think before acting. Positive parenting style dimensions (warmth, regularity, and support independence) has a higher achievement than the dimensions negati f (denial, irregularity, and coercion).Results of the study found no association and the influence of mothers on the independence of adolescent personality. However, the regression test found the influence of mother's personality on mother's nurturing style and only the large family to the independence of rural adolescents.